2010
DOI: 10.1002/jms.1741
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation kinetics and byproducts identification of the Aflatoxin B1 in aqueous medium by ultra‐performance liquid chromatography–quadrupole time‐of‐flight mass spectrometry

Abstract: A photodegradation study of Aflatoxin B(1) (AFB(1)) in water solution was performed under UV irradiation at different AFB(1) initial concentrations and UV irradiation intensities. The effect of UV intensity on the AFB(1) photodegradation ratio is dominative, when compared with AFB(1) initial concentration. The photodegradation of AFB(1) was proved to follow first-order reaction kinetics (R(2) > or = 0.99). Three photodegradation products, i.e. P(1) (C(17)H(14)O(7)), P(2) (C(16)H(14)O(6)) and P(3) (C(16)H(12)O(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 13 publications
3
53
0
Order By: Relevance
“…The structures of the UV degradation products of AFB 1 have been elucidated, and the toxicity of the degradation products has been examined by the AMES test. It was found that exposure to UV caused the loss of double bond in the terminal furan ring [21] and the degradation products completely lost the mutagenic activity [26]. In this study, all the five degradation products lost their double bond in the terminal furan ring and product A even completely lost the entire ring.…”
Section: Toxicity Analysismentioning
confidence: 83%
See 3 more Smart Citations
“…The structures of the UV degradation products of AFB 1 have been elucidated, and the toxicity of the degradation products has been examined by the AMES test. It was found that exposure to UV caused the loss of double bond in the terminal furan ring [21] and the degradation products completely lost the mutagenic activity [26]. In this study, all the five degradation products lost their double bond in the terminal furan ring and product A even completely lost the entire ring.…”
Section: Toxicity Analysismentioning
confidence: 83%
“…Exposure to Co 60 gamma ray resulted in more than 20 degradation products [27], and ozonolysis of AFB 1 in acetonitrile and water yielded a total of 13 and 6 products, respectively [28,29]. Meanwhile, UV irradiation could also degrade AFB 1 , but only three products were resolved [21]. By comparing with these reports, it could be seen that the degradation products of AFB 1 by low-temperature RF plasma have never been reported before, implying that the plasma possibly exerted its degradation effect through different ways or different free radicals.…”
Section: Separation Of Degradation Productsmentioning
confidence: 93%
See 2 more Smart Citations
“…UV irradiation has been discovered for many years as an effective physical method to destroy aflatoxins for its photosensitive property [15] .Rate of degradation was a function of the film thickness and depth of penetration of the rays when operating conditions were held constant [16]. Because aflatoxins are photosensitive [15], our aim was to study the detection of aflatoxin M1 and detoxification of it in milk using ultraviolet (UV) energy at different distance between UV source and milk and different volumes of milk at different times.…”
Section: Introductionmentioning
confidence: 99%